Development of soft cookie from pregelatinized banana flour and germinated brown rice - Leelwat, B.; Jaengarunjiramanee, N.; Pischom, A. (International Journal of Agricultural Technology, 2022)
The soft cookie from pregelatinized banana flour and germinated brown rice was developed by studying the optimum ratio between pregelatinized banana flour and germinated brown rice. The optimum ratio between pregelatinized banana flour and germinated brown rice (80:20 by weight) was determined by pasting characteristic and solubility property. The selected ratio of mixed flour was subsequently substituted to wheat flour as 0, 50, 75 and 100 percent in soft cookie formula. The sensory evaluation was performed and the result showed that 75 percent substitution in soft cookies got the highest overall acceptability among the others and the texture of soft cookie showed the hardness of 0.270 ± 0.03 gram force. After that the optimum percentage of sugar was studied by varying the reduction of sugar percentage from the standard formula as 10, 20, and 30 percent. The results showed that 30 percent of sugar reduction got the highest overall acceptability from sensory evaluation. The texture of soft cookie showed the hardness of 1.205 ± 0.30 gram force and specific volume of 1.902 cm3/g. The consumer’s decision purchasing and consumer acceptance test using 80 general participants were conducted and the results showed that 31.3% of consumers will definitely buy the products. Additionally, the consumers gave the hedonic score in terms of appearance, colors, and flavor as like slightly to like moderately and in the attributes of taste, texture, and overall acceptability were scored as like very much to like extremely